PEMBUATAN BASIS DATA BERBASIS EXCEL DAN PEMANFAATANNYA DALAM PEMETAAN POTENSI SUMBER DAYA MANUSIA - Animah, Animah; Akram, Akram; Martiningsih, Rr. Sri Pancawati (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Currently, all activities are related to digitalization. On the one hand, changes from manual to digitalization have a positive impact if accompanied by an increase in human resource competence. On the other hand, if there is no increase in human resources related to digitalization, it will bring setbacks. Villages are the spearhead of a country. If village officials and the government in the village do not understand digitalization, then it is certain that the country will experience a seatback. A database is an output that results from digitalization. The most crucial thing in a database at the village level is regarding population, whether the database can provide the total number, productive age, education, variety of businesses. If the simplest and most important database is available, the service will be faster, and decision-making will improve.